INTERFAITH DIALOGUE IN INDIA - Suresh, A (Journal of Dharma, 2000)
India has the privilege and fortune of being the mother and matrix of many religious traditions. Hinduism, Buddhism, Jainism and Sikhism are born and have grown in India. Zoroastrianism (the Parsi religion), though not originated in India, exists only in India today. Judaism struck roots in India long before the common era. Christianity came to South India just after the death and resurrection of its founder Jesus Christ. And Islam also came to India immediately after the death of prophet Muhammad.